CRYSTALLOGRAPHIC ORIENTATIONS OF HIGH-ANGLE GRAIN BOUNDARIES IN DYNAMICALLY RECRYSTALLIZED QUARTZ: FIRST RESULTS - Kuntcheva B.; Kruhl J.H.; Kunze K. (My University, 2006)
The crystallography and geometry of high-angle grain boundaries from dynamically recrystallized quartz have been studied. On the basis of combined electron backscatter diffraction and universal stage measurements, the complete crystallographic orientation of the grain boundaries could be calculated. The u-stage rotation of the grain boundaries to a vertical position reveals that they are never curved but always consist of straight segments. Our results show that these segments preferentially occupy rhombohedral, trapezohedral and bipyramidal orientations, i.e., orientations in a ∼ 25–50° girdle to the c-axis. A specific, albeit low, number of segments with special crystallographic orientation, with respect to a neighbouring quartz grain, often shows another special orientation with respect to the other neighbouring grain. Preferred combinations of grain boundary orientations related to both neighbouring grains are (i) low-index rhombohedral and high index trapezohedral, (ii) low-index bipyramidal and low-index trapezohedral or high-index rhombohedral, and (iii) low-index trapezohedral and low or high index trapezohedral. In certain cases, such as at triple junctions, the boundaries occupy specific trapezohedral orientations with a constant angle to the c-axis. This argues for energy isotropy of trapezohedral planes with the same angle to the quartz c-axis. In general, good match coincidence site lattice (CSL) orientations are not preferentially occupied so that most of the studied grain boundaries represent general boundaries. The formation of straight segments in special crystallographic orientations indicates the crystallographic control and implies an energy reduction of certain general boundaries.